Food markets and diets in the Democratic Republic of the Congo: A geographical overview (2004–2005) - Marivoet, Wim (SAGE Publications, 2024)
To inform policy makers concerned with food security, this paper relies on the 1–2–3 household survey (2004–2005) to provide a geographical overview of Congo’s food markets and dietary status. The results of this descriptive study point to inefficient domestic food markets, with Kinshasa being a case in point: it is deficient, poorly connected to its hinterland and highly dependent on imports. Food markets in the Kasaï provinces and the northeastern region are two minor exceptions, while the most competitive food producers are found in Équateur and North Kivu. Despite differential access, five diet types can be identified, with the most energy rich (cassava/palm oil) being consumed in Maniema, Orientale, Équateur, and rural Bas-Congo. In contrast, households in South Kivu and Kinshasa suffer from large calorie deficiencies, which is due to low purchasing power for the former and relatively higher food prices and more demanding social norms for the latter.